2020
DOI: 10.1155/2020/1840415
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Validation, and Functional Annotations of Genome-Wide Profile Variation between Melanocytic Nevus and Malignant Melanoma

Abstract: Cutaneous melanoma (CM) is known as an aggressive malignant cancer; some of which are directly derived from melanocytic nevi, which have been attracting growing attention from the last decades. This study focused on comprehensive identification, validation, and functional annotations of prognostic differentially expressed genes (DEGs) between melanocytic nevus and malignant melanoma in genome-wide profiles. DEGs were obtained using three chip datasets from GEO database to identify after standardization annotat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
1
5
0
1
Order By: Relevance
“… 13 Relative paper clarified that six hub genes, including FABP5, IVL, KRT6A, KRT15, KRT16, and TIMP2, were significant value in predicting transformation from nevi to melanoma. 14 , 15 In addition, in this case report, we found that the mutation of KRT16 in PC correlated with the occurrence and transformation of melanoma. To clarify whether KRT16 mutation is closely related to the conversion of PC to MM is the key point of our next work.…”
Section: Discussionsupporting
confidence: 55%
“… 13 Relative paper clarified that six hub genes, including FABP5, IVL, KRT6A, KRT15, KRT16, and TIMP2, were significant value in predicting transformation from nevi to melanoma. 14 , 15 In addition, in this case report, we found that the mutation of KRT16 in PC correlated with the occurrence and transformation of melanoma. To clarify whether KRT16 mutation is closely related to the conversion of PC to MM is the key point of our next work.…”
Section: Discussionsupporting
confidence: 55%
“…Whether these drugs will also inhibit keratinocyte-derived signals that affect immune cell and melanocyte recruitment is unclear and represents an unexplored area for drug targeting in vitiligo. Interestingly, stress keratinocytes expressing KRT6 , KRT16 , and S100A8/9 have been identified in the human epidermis of psoriasis and melanomas, raising the possibility that they can play a wide variety of roles in the diseased skin TME ( 57 59 ). Further studies on stress keratinocytes will improve our understanding of how keratinocyte states affect the TME and contribute to disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, stress keratinocytes expressing KRT6, 16 and S100A8/9 have been identified in the human epidermis of psoriasis and melanomas, raising the possibility that they can play a wide variety of roles in the diseased skin tissue microenvironment (57)(58)(59). Further studies on stress keratinocytes will improve our understanding how keratinocyte states affect the tissue microenvironment and contribute to disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%